Status of Seaweed Research in Kenya - Mwayuli, G.A.; Manohar, S.; Oyieke, H.A (Africa Environmental Review Journal, 2004)
Seaweeds are an important natural resource with a lot of ecological and economic uses. Kenya has about 400 identified seaweed species. This paper highlights some of the global uses of seaweeds and discusses the status of seaweed research in Kenya obtained from a bibliometric survey. Most research has been undertaken by non-Kenyan researchers and has concentrated on taxonomy/systematics and ecology. Limited research on distribution ecology, zonation and potential Use of some seaweed species has also been undertaken. There is need for more research on diversity and ecology, especially of the deeper species, the potential use of the seaweed in pharmaceutical industry, medicine, agriculture and environmental monitoring; screening of seaweeds for natural products and seaweed mariculture. The government should take more interest in this important yet overlooked resource.